2019
DOI: 10.1038/s41598-019-46394-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-target Effects of Naphthalene on the Soil Microbial Biomass and Bacterial Communities in the Subalpine Forests of Western China

Abstract: Naphthalene is a biocide of soil fauna, particularly of soil arthropods, that has been widely applied to test the functional roles of soil fauna in soil processes. However, whether the use of naphthalene to expel soil fauna has a non-target effect on soil bacteria in subalpine forests remains unclear. We conducted a naphthalene treatment experiment to explore the effects of naphthalene on the soil bacterial community in subalpine forest soil. The results suggested that naphthalene treatment (at 100 g.m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Some researchers have concluded that the effect of insecticide experiments (naphthalene) tends to be double that of the mean graded mesh effect (2.45 versus 1.19) on litter decomposition rate [24], and a similar result was also found in a recent meta-analysis [25]. This discrepancy between the two methods can result from either (1) the incomplete exclusion of animals when using the graded mesh bags or (2) the presence of enhanced microbial activity when using naphthalene with organic carbon additives [20,22]. Thus, we do not have a quantitative and clear understanding of the effects of the application of naphthalene to the soil surface on soil fungal community composition.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Some researchers have concluded that the effect of insecticide experiments (naphthalene) tends to be double that of the mean graded mesh effect (2.45 versus 1.19) on litter decomposition rate [24], and a similar result was also found in a recent meta-analysis [25]. This discrepancy between the two methods can result from either (1) the incomplete exclusion of animals when using the graded mesh bags or (2) the presence of enhanced microbial activity when using naphthalene with organic carbon additives [20,22]. Thus, we do not have a quantitative and clear understanding of the effects of the application of naphthalene to the soil surface on soil fungal community composition.…”
Section: Introductionsupporting
confidence: 55%
“…Research conducted in a tallgrass prairie concluded that the application of naphthalene was effective in reducing soil micro-arthropods and had negligible direct effects on soil microbial abundance and C dynamics [20]. However, studies from an alpine forest ecosystem located on the eastern Tibetan Plateau of China implied that naphthalene treatment might have affected active bacterial community abundance but not soil bacterial community structure [22]. Moreover, other researchers have demonstrated that naphthalene treatments not only significantly reduce the density and species richness of soil arthropods but also indirectly influence soil C-, N-, and P-degrading enzymes [16,23].…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acyls compounds were the component of soil microbial cell membrane, and the increase of soil pH was beneficial to the accumulation of fatty acyls, which in turn improved the reproductive ability of microorganisms (Warren, 2021). Naphthalenes and piperidines compounds could effectively inhibit pathogen reproduction, control pests and diseases, and increase the number and diversity of beneficial soil microorganisms (Lan et al, 2019;Boadi et al, 2021;León-Morales et al, 2022). Azoles compounds were a class of antifungal compounds that played an important role in the control of plant pathogens (Rhijn et al, 2021;Sun et al, 2022b).…”
Section: Analysis Of Characteristic Compounds In Rhizosphere Soil Of ...mentioning
confidence: 99%
“…We did not find a significant difference in effects on invertebrate effect sizes between physical and chemical protocols. The potential non‐target effects of chemicals such as naphthalene on soil organisms and environments (Lan et al., 2020), however, leads us to advocate the use of physical exclusion methods (Lan et al., 2019), particularly in highly stochastic tropical rainforests and in regions with high precipitation.…”
Section: Future Workmentioning
confidence: 99%